(3EjVGM GdaJGhi aj GdfcJ GdeJYdbg HGdMGhjs - (3GdfGTQj , YHO Gddg Hf eMeO Hf YHO Gddg Hf YeQ Hf CHh HcQ Hf YeQ, CHh GdaJhM,J (B814 (3g` s
(3ChdgG (B:s
(3Ghd GdcJGH s
(3BNQgG (B:s
(3Ghd HGH GdUdM s
(3GdeDda ef YdeGA GdbQf GdJGSYs
(3ef fSNI cJHJ Sfg (B871(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQM s
Keywords: (3Gdabg GdTGaYjs